Editorial: Seeing convergent margin processes through metamorphism - Chen, Y; Li, Q; Zhang, G; Tsujimori, T; Palin, RM (Frontiers Media, 2022)
Plate convergence can induce large-scale metamorphism and magmatism, reshape large parts of continental margins, and subsequently change regional climate and biodiversity. Metamorphic rocks in orogenic belts commonly record different metamorphic evolutions and temporal-spatial distributions at the regional scale, which are strongly influenced by convergent processes through time. In some cases, ultrahigh-pressure (UHP) and ultrahigh-temperature (UHT) metamorphic rocks are observed at both ancient and young convergent plate margins, marking the operation of extreme tectonism in the regime of plate tectonics. This Research Topic aims to understand how regional metamorphism operated at convergent plate margins through the study of field and petrographic observations, geochemical and petrological analysis, high-pressure experiments, and thermodynamic modeling. The scope is to gather new ideas and interpretations on the structure and processes of convergent plate margins.